Умови динамічної стійкості та якість перехідних процесів мережевих пневматичних регуляторів літальних апартів - Хлистун, Олександр Іванович; Бадах, Валерій Миколайович; Єременко, Роман Олександрович; Khlystun, Oleksandr; Badakh, Valerii; Yeremenko, Roman (Запоріжжя : Видавничий дім «Гельветика», 2025)
UA: У статті представлено дослідження умов динамічної стійкості та якості перехідних процесів мережевих пневматичних клапанів (МПК) літальних апартів, їх зв'язок зі структурною схемою і особливостями конструкції. Набув розвитку метод моделювання перехідних процесів у сучасних авіаційних МПК, заснований на рівняннях термодинаміки тіла змінної маси та методах теорії лінійних динамічних систем. На основі органоструктури та конструктивної схеми визначено основні збурювальні впливи на робочий процес у МПК. Розроблено математичну модель динаміки перехідних процесів, яка враховує структурну схему та особливості конструкції МПК, визначено структуру і параметри передавальної функції, розроблено алгоритми та обчислювальні програми на мові MATLAB, які дозволили виявити значення конструктивних параметрів за яких процес регулювання є стійким. Встановлено залежність показників якості та запасів стійкості перехідного процесу МПК від коефіцієнта підсилення коригувального пристрою. /// EN: The article presents a study of the conditions of dynamic stability and quality of transient processes of network pneumatic valves (NPV) of aircraft, their relationship with the structural scheme and design features. A method of modeling transient processes in modern aviation NPV has been developed, based on the equations of thermodynamics of a body of variable mass and methods of the theory of linear dynamic systems. Based on the organizational structure and structural scheme, the main disruptive influences on the work process in the NPV were identified. A mathematical model of the dynamics of transient processes has been developed, which is presented in the form of a system of pneumatic and mechanical links with lumped parameters, and takes into account the structural scheme and design features of the NPV; the structure and parameters of the transfer function have been determined; algorithms and computational programs in the MATLAB language have been developed, which allowed us to identify the values of the design parameters for which the control process is stable. According to the design data of the pressure reducer installed in the aircraft pneumatic system, the parameters of the transfer functions of the pneumatic chamber and the sensitive element are determined. According to the characteristic equation, for the system gain coefficient (SGC), a root hodograph is constructed and the region of positive values of SGC is established, in which the process of regulating the pressure reducer is stable. It is shown that changing the gain of the correction device significantly affects the quality indicators and stability reserves of the regulator and the system as a whole. The obtained estimates of the quality of the regulation process show that the presented regulator model can be used to optimize the quality of its transient process by selecting the necessary values of the parameters of the structural elements of the regulator.
Dynamic Stability Conditions and Quality of Transition Process of an Aircraft Network Pneumatic Valves
Keywords: пневматична система; літальний апарат; клапан тиску; математична модель; передавальна функція; структурна схема; запас стійкості; pneumatic system; aircraft; pressure valve; mathematical model; transfer function; structural diagram; stability margin